A sustainable trend in COVID-19 research: An environmental perspective - Vadiati, Meysam; Ghasemi, Leyla; Samani, Saeideh; Islam, Md. Aminul; Ahmadi, Arman; Khaleghi, Saeid; Movarej, Maryam; Gorgij, Alireza Docheshmeh; Kisi, Ozgur; Davoodi, Shahla; Dhama, Kuldeep; Tiwari, Ananda; et al. (Frontiers in Environmental Science, 2023)
Coronavirus disease 2019 (COVID-19) has spread across the globe producing hundreds of thousands of deaths, shutting down economies, closing borders and causing havoc on an unprecedented scale. Its potent effects have earned the attention of researchers in different fields worldwide. Among them, authors from different countries have published numerous research articles based on the environmental concepts of COVID-19. The environment is considered an essential receptor in the COVID-19 pandemic, and it is academically significant to look into publications to follow the pathway of hot topics of research and upcoming trends in studies. Reviewing the literature can therefore provide valuable information regarding the strengths and weaknesses in facing the COVID-19 pandemic, considering the environmental viewpoint. The present study categorizes the understanding caused by environmental and COVID-19-related published papers in the Scopus metadata from 2020 to 2021. VOSviewer is a promising bibliometric tool used to analyze the publications with keywords “COVID-19*” and “Environment.” Then, a narrative evaluation is utilized to delineate the most interesting research topics. Co-occurrence analysis is applied in this research, which further characterizes different thematic clusters. The published literature mainly focused on four central cluster environmental concepts: air pollution, epidemiology and virus transmission, water and wastewater, and environmental policy. It also reveals that environmental policy has gained worldwide interest, with the main keyword “management” and includes keywords like waste management, sustainability, governance, ecosystem, and climate change. Although these keywords could also appear in other environmental policy-related research studies, the importance of the COVID-19 pandemic requires such comprehensive research. The fourth cluster involves governance and management concerns encountered during the pandemic. Mapping the research topics in different clusters will pave the way for researchers to view future potential ideas and studies better. The scope for further research needs from the perspective of environmental concepts is reviewed and recommended, which can expand the vital role and value of environmental sciences in alerting, observing, and COVID-19 prediction for all four clusters. In other words, the research trend would shift from qualitative studies and perspectives to quantitative ones.